Investigating Efl Students’ Engagement And Responses In Learning English Vocabulary Through Mind-Mapping Strategy - Kurniawan, Aldino Hardanto (Jurnal Ilmiah Wahana Pendidikan, 2024)
Mind mapping is a promising strategy designed in connecting vocabulary with learning that can improve student behavior, cognition, and emotions so that mind-mapping learning can run in accordance with the working system of the human brain. Vocabulary is a core component of listening, speaking, reading, and writing. Vocabulary is very important to learn for students who want to master a language. Student engagement is the level of student involvement in academic activities such as attending class, working on assignments, taking part in discussions, and asking questions in class. This study aims to involve students in learning English Vocabulary through mind mapping strategies and obtain student responses to the use of mind mapping strategies in learning English vocabulary. The current research uses qualitative research with Classroom Action Research (CAR) with data collection through interviews, observation, and documentation. The data is analyzed by thematic analysis. This study was conducted in a junior high school in Bekasi in grade 8 and involved five students in collecting interview data. It can be found that there are 2 cycles to be carried out in the study consisting of Cycle 1 (First and second meeting) and Cycle 2 (first and second meeting). Cycle 1 of the first and second meetings showed that students were very enthusiastic and less enthusiastic in learning mind-mapping with English vocabulary. In cycle 2, the first and second meetings showed that students remained enthusiastic about the material presented and considered the mind-mapping material easy to master.